Formulation of Regional Regulations Based on Laws and Regulations - Tuasikal, Hadi; Homer, Yan Piet (Faculty of Law, Universitas Muhammadiyah Sorong, 2024)
This study aims to analyze the principles, procedures, and authorities in the formation of Local Regulations (Perda) by local governments in Indonesia in accordance with the mandate of the 1945 Constitution of the Republic of Indonesia and Law Number 32 of 2004. Based on these provisions, local regulations are important instruments that support the implementation of regional autonomy, where the local government and the Regional People's Representative Council (DPRD) jointly have the legislative authority to formulate local regulations that regulate regional household affairs and the interests of local communities. The research method used is normative juridical with a literature approach, examining primary legal sources such as laws and regulations, as well as secondary literature from relevant journals and articles. The results show that local regulations are formed through joint approval between the DPRD and the regional head, taking into account philosophical, juridical, and sociological foundations that reflect the values of Pancasila and applicable legal norms. The novelty of this research is the emphasis on the importance of the DPRD's control function over the implementation of Perda and APBD, as well as the identification of various challenges in the regional legislative process that are sometimes affected by local political constraints. In conclusion, local regulations play a significant role in supporting regional autonomy, but must be designed so that they do not conflict with the public interest and higher regulations.